Tinjauan Yuridis Terhadap Tindak Pidana Korupsi Dana Desa: Studi Kasus Putusan (Nomor 59/Pid.Sus-Tpk/2019/Pn Mdn) - Siti Rohaya (Albayan Journal of Islam and Muslim Societies, 2024)
This research discusses the criminal act of village fund corruption committed by village officials, using the case study of Decision Number 59/Pid.Sus-TPK/2019/PN Mdn. The focus of the study is to analyze the legal regulations related to village fund corruption, the application of the elements of corruption in the case, as well as the legal considerations of the judge in rendering the verdict. This study employs a normative juridical method through statutory and literature approaches, supplemented by field interviews. The findings indicate that the misuse of village funds often occurs due to weak supervision, limited legal understanding, and low integrity of village officials. The court's ruling refers to Articles 2 and 3 of the Anti-Corruption Law (UU Tipikor), considering elements such as illegality, abuse of authority, and state financial losses. In addition to juridical aspects, the judge also considered the socioeconomic background of the defendant. This research underscores the importance of reforming the village financial management system to ensure greater transparency and accountability, strengthening the legal capacity of village officials, and enhancing community participation in overseeing village fund utilization. Moreover, strong commitment and synergy among law enforcement agencies such as the Corruption Eradication Commission (KPK), the Prosecutor’s Office, and the Audit Board of Indonesia (BPK) are essential to ensure the effectiveness and sustainability of anti-corruption efforts at the village level. This case serves as a significant example of how legal approaches can be strategic instruments in upholding justice and protecting citizens' rights to corruption-free development.